The words for colors in Croatian: different means of lexicon extension - Jelaska, Zrinka; Cvikić, Lidija (2005)
This paper deals with Croatian words for colors. The main part of the paper examines means of lexicon extension. Etymological analysis shows that the first means of lexicon extension are already found in the historical development of basic Croatian color terms. Another set of principles of lexicon extension, based on the reaction of the observer, as well as on social connotations (e.g. prestige, manipulation), are found in the more developed Croatian color lexicon.
Projekt MZOS
ENG